Índice de condição baseado em defeitos superficiais para gerência de pavimentos urbanos - Albuquerque, Tairone Paz e (2017)
The serviceability evaluation through the pavement condition index can be a tool aided to make a decision of maintenance and rehabilitation, and optimize the financial resources. Several indexes of pavement conditions were developed for intercity roads of long-distance. However, in order for them to be used on urban roads, they must be adjusted and calibrated according to the local conditions. It is important to analyze the behavior of the pavement in order to collect the most relevant distresses of the urban pavement and, based on this, develop an Urban Pavement Condition Index that represents the most significant surface distresses for a network-level analysis . The main objective of this study was to calibrate and to validate a propose index for the city of Joao Pessoa and to compare it with some pavements conditions indexes.The work method was developed in nine steps: i) literature review; ii) characterization of the study area; (iii) definition of sampling; iv) definition of evaluation guidelines; v) Training and definition of the group of evaluators; vi) Collection of surface distresses and subjective evaluation of pavement; vii) data processing; viii) development of the urban pavement condition index; ix) comparative analysis of urban pavement condition indexes. Regarding the homogeneity of the panel of evaluators, it was verified that 93% of the subjective evaluations showed a coefficient of variation lower than 15%, characterizing a low dispersion between the scores attributed by the evaluators. Of the sixteen types of surface distresses defined for collection data, only six distresses were statistically significant to explain the current serviceability value (VSA) of the evaluated segments. The urban pavement condition index was developed according to the criteria of test F, test t-Student and all statistical assumptions for the development of the multilinear regression index. It was verified that the indexes chosen to carry out the comparative, having as reference the VSA, presented great variations in the classification of the pavement segments. The Urban Pavement Condition Index of Joao Pessoa (ICPUJP) presented the lowest absolute mean relative error (MARE = 16.23%) and the linear correlation with higher strength (R = 0.93). The others indices showed high values in the absolute mean of relative errors at the classification of the condition of pavements regular to the worst. However, in the condition of good and excellent pavement, the indexes (ICPU and DMINL) presented an absolute mean of relative errors smaller than the others, but next to ICPUJP. Among the evaluated indices, there is evidence that the ICPUJP obtained the best performance in the classification of the condition of the pavement of Joao Pessoa, being, therefore, a effective tool to evaluate the condition of pavement of the urban road network and to assist at the activities of Maintenance and rehabilitation.